2016
DOI: 10.11118/actaun201664020379
|View full text |Cite
|
Sign up to set email alerts
|

Damage of the Remaining Stands Caused by Various Types of Logging Technology

Abstract: Forest harvesting causes a lot of damage, which results in damage of the remaining stand. These damages have different character. Their origin, range, and type is affected by the type of machinery, harvesting technology and the machine operator. This paper was focused on the negative impact of three types of forest harvesting technologies to the remaining stand. We considered wheeled skidder technology, and CTL technology with wheeled and tracked chassis. The harvest in stands varied between 21 and 52%, with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 4 publications
(3 reference statements)
0
9
0
Order By: Relevance
“…[35] states wounds at tree roots were from 10 to 200 cm 2 large in mixed beech-oak stands. [39] compared the mean size of wounds that occurred during forest operations performed by skidders and harvesters. He revealed the smallest mean sizes of 134.21 and 200 cm 2 in stands, where a tracked harvester was applied (spruce-thinning).…”
Section: Discussionmentioning
confidence: 99%
“…[35] states wounds at tree roots were from 10 to 200 cm 2 large in mixed beech-oak stands. [39] compared the mean size of wounds that occurred during forest operations performed by skidders and harvesters. He revealed the smallest mean sizes of 134.21 and 200 cm 2 in stands, where a tracked harvester was applied (spruce-thinning).…”
Section: Discussionmentioning
confidence: 99%
“…110 y.o. oak were skidded [87]. The same authors observed that a higher thinning (or shelterwood cutting) intensity can cause a higher level of damage.…”
Section: Short Wood System Vs Long Wood Systemmentioning
confidence: 93%
“…and younger stands (30-35 y.o.) or species: oak or spruce [87]. Cudzik et al [48] confirmed a lower level of damage, 4-6% in thinned stands, where CTL was used, and 9-12% for chainsaw felling with skidding in the late thinning of pine stands.…”
Section: Short Wood System Vs Long Wood Systemmentioning
confidence: 99%
See 2 more Smart Citations